3D Printing: Electrodeposition‐based 3D Printing of Metallic Microarchitectures with Controlled Internal Structures (Small 32/2015). Issue 32 (20th August 2015) - Seol, Seung Kwon; Kim, Daeho; Lee, Sanghyeon; Kim, Jung Hyun; Chang, Won Suk; Kim, Ji Tae
<x xml:space="preserve">Abstract</x> Freestanding copper 3D microarchitectures are printed by S. K. Seol and co‐workers using the meniscus‐guided electrodeposition method, which utilizes the meniscus as a local electrolyte bath. On page 3896, when the nozzle touches the substrate, an electrolyte meniscus is created between its opening and the conductive substrate surface. With an appropriate electrical potential applied between the microelectrode and the substrate, copper electrodeposition occurs on the substrate. Precise control of the nozzle enables the printing of complex 3D microarchitectures with well‐defined geometries and positions.